Efeito do extrato de Cissampelos sympodialis Eich. em ratos submetidos à hipertensão pulmonar induzida pela monocrotalina - Magalhães, Daniel Marcelo Silva (2009)
Cissampelos sympodialis Eichl. (Menispermaceae) is a plant species used in popular medicine in Northeast of Brazil, whose pharmacological effects shows a great potential in treatment of respiratory diseases. Fosfodiesterase inhibition and smooth muscle relaxant effects are attributed to its leaves extract. Sildenafil, an oral fosfodiesterase type 5 inhibitor, is a drug used in treatment of pulmonary hypertension by vasodilatory effects through a cyclic guanosine 3´,5´-monophosphate (cGMP) dependent mechanism. This study was designed to investigate chronic effects of Cissampelos sympodialis extract in monocrotaline (MCT) induced pulmonary hypertension in rats, using sildenafil as a reference drug. After a single subcutaneous injection of MCT, rats were randomized to receive repeated administration of saline, sildenafil, Cissampelos sympodialis extract or both twice a day for 4 weeks. In the last day of treatment, animals were submitted to a median toracotomy to access pulmonary pressure. Four weeks after MCT injection, there was a significant development of pulmonary hypertension (60.19 ± 6.81), in contrast with SHAM group (32.77 ± 1.80). The increases in pulmonary mean pressure, ratio of right ventricular weight to body weight and thickening of the precapillary artery wall were significantly attenuated in the Cissampelos sympodialis extract (37.40 ± 3.76; 0.63 ± 0.04; 57.33 ± 5.04; respectively) and Sildenafil groups (34.57 ± 3.85; 0.68 ± 0.04; 57.00 ± 4.07; respectively), when compared to control group (52.65 ± 4.05; 1.14 ± 0.07; 89.43 ± 1.29; respectively). Combination therapy (32.16 ± 3.65; 0.86 ± 0.02; 64.62 ± 7.28; respectively) with sildenafil and extract had no additive effects in this model. These results suggest that therapy with oral Cissampelos sympodialis extract and sildenafil attenuates the development of monocrotaline induced pulmonary hypertension and that combination therapy has no additional effects compared with sildenafil or extract given alone.